1986
DOI: 10.1111/j.1600-0447.1986.tb02696.x
|View full text |Cite
|
Sign up to set email alerts
|

Twenty‐four‐hour serum levels of T4 and T3 in relation to decreased TSH serum levels and decreased TSH response to TRH in affective disorders

Abstract: The serum levels of thyroxine and triiodothyronine (T4 and T3) were investigated at 10 different time points during a 24 h period in 31 inpatients meeting the RDC criteria for acute major depressive disorder. Twenty-three of these patients were also reinvestigated in a state of partial or complete remission. The results show that there was no significant difference in T4 or T3 levels during the 24 h period between depressed patients and 32 healthy controls despite significantly decreased TSH levels and TSH res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
1
1

Year Published

1989
1989
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(10 citation statements)
references
References 42 publications
2
6
1
1
Order By: Relevance
“…This is similar to the findings of Linnoila et al [2] and Orsulak et al [4], On the other hand, other studies on T3 in depressed patients reported it normal [3,9], Furthermore, Spratt et al [10] reported increased T3 and T4 levels in a series of 646 psychiatric patients that included depressed subjects.…”
Section: Discussionsupporting
confidence: 78%
“…This is similar to the findings of Linnoila et al [2] and Orsulak et al [4], On the other hand, other studies on T3 in depressed patients reported it normal [3,9], Furthermore, Spratt et al [10] reported increased T3 and T4 levels in a series of 646 psychiatric patients that included depressed subjects.…”
Section: Discussionsupporting
confidence: 78%
“…Concentrations of T4 or FT4 are commonly increased during depression (324329) and revert after recovery from MD, irrespective of the modality of treatment (330339). Despite the presence of elevated T4 concentrations TSH levels tend to be normal in depressive patients, but circadian variation of TSH concentration is impaired (339342) and the response to TRH test is blunted (323). Both total and free T3 concentrations are reduced in MD (175, 176, 343), but elevated in bipolar I disorder (237, 344).…”
Section: Thyroid Allostasis In Various Physiological and Pathologicalmentioning
confidence: 99%
“…Concerning reports on the response of prolactin to dexamethasone administration (Rupprecht et al -1988) describing endocrine as well as clinical similarities between minor depression and psychosexual dysfunction, this study reveals comparable results on thyroid hormones. In patients with major depression some authors noted lower (Orsulak et al -1985) or normal T, and normal T4 levels (Unden et al -1986) as well as decreased levels of TSH (Unden et al -1986).…”
Section: Discussionmentioning
confidence: 99%
“…During depression normal (Unden et al 1986) or lowered T3 levels (Orsulak et al -1985) and lowered TSH levels (Unden et al -1986) were reported. More consistent, however, is the blunted response of TSH to TRH depending on the depressive state (Agren and Wide -1986).…”
Section: Introductionmentioning
confidence: 99%